The Effect of Training on Employee Performance - Citra Gitar Mahardika; Bachruddin Saleh Luturlean (Almana : Jurnal Manajemen dan Bisnis, 2020)
Human resources play the most important and potential role for the success of a company considering that human resources are the determinants of company activities both in planning, organizing, and making decisions. To make this happen, one of the efforts a company can make to improve the quality of its employees is by conducting training. This research is quantitative. This type of research used is descriptive and causal methods. The purpose of this study was to determine the effect of training on the performance of PT. Astra International Tbk - Toyota Sales Operation (AUTO2000) Soekarno Hatta Bandung Branch. The type of sample used is a saturated sampling. Data collection was carried out by distributing questionnaires to 51 people. The data analysis technique used is a simple regression analysis. Based on the results of simple linear regression analysis, training improves employee performance by 0.441. training affects the performance of technician employees by 65.1% and 34.9% is influenced by other factors. The advice given by the writer for the company is to hold a workshop or motivational seminar and further increase the type of training material provided.